Blood scarcity at the blood banks during COVID-19 pandemic and strategies to promote blood donations: current knowledge and futuristic vision. Issue 1 (1st January 2021) - Sah, Ranjit; Rodriguez-Morales, Alfonso J.; Fathah, Zareena; Shrestha, Sunil; Mehta, Rachana; Khatiwada, Asmita Priyadarshini; Tiwari, Ruchi; Sharun, Khan; Mohapatra, Ranjan K; Dhawan, Manish; Emran, Talha Bin; Dhama, Kuldeep
ABSTRACT: The course of the coronavirus disease (COVID-19) pandemic has significantly affected the healthcare systems in multiple ways, the programs of control and the management of patients with other infectious diseases as well as with chronic and acute non-communicable diseases, including those conditions requiring blood transfusions. Blood donations have been decreasing over time in multiple countries with their expected consequences. Although the spread of SARS-CoV-2 has not been detected via blood transfusion, the increasing fear and anxiety among communities have led to a substantial decrease in blood donations. Several research groups have raised concerns about the consequences associated with the scarcity of blood. However, it is critical to understand the underlying causes of the sharp decline in blood donations, as well as the consequences. Hence, we discuss the impact of blood scarcity at the blood banks during the COVID-19 pandemic as well as strategies to promote blood donations, given the experience in some countries with this situation.